2011
DOI: 10.1128/aem.02669-10
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Wickerhamomyces anomalus and Lactobacillus plantarum during Sourdough Fermentation: Identification of Novel Compounds and Long-Term Effect during Storage of Wheat Bread

Abstract: This study aimed at investigating the antifungal activity of Wickerhamomyces anomalus and sourdough lactic acid bacteria to extend the shelf life of wheat flour bread. The antifungal activity was assayed by agar diffusion, growth rate inhibition, and conidial germination assays, using Penicillium roqueforti DPPMAF1 as the indicator fungus. Sourdough fermented by Lactobacillus plantarum 1A7 (S1A7) and dough fermented by W. anomalus LCF1695 (D1695) were selected and characterized. The water/salt-soluble extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
92
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 40 publications
1
92
2
3
Order By: Relevance
“…The antifungal activity of metabolites from lactic acid bacteria in bread has, to date, been attributed not to a single compound but, rather, to their synergistic activity with substrate-or yeastderived compounds (4,5,8,10). This study demonstrated that enzymatic and microbial activities generate antifungal hydroxy fatty acids from linoleic acid.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The antifungal activity of metabolites from lactic acid bacteria in bread has, to date, been attributed not to a single compound but, rather, to their synergistic activity with substrate-or yeastderived compounds (4,5,8,10). This study demonstrated that enzymatic and microbial activities generate antifungal hydroxy fatty acids from linoleic acid.…”
Section: Discussionmentioning
confidence: 79%
“…ourdough bread has an extended mold-free storage life compared to that of conventionally leavened products (1, 2), and metabolites from specific strains of lactobacilli contribute to the prolonged storage life of sourdough bread (3,4,5). While the fermentation microbiota of traditional sourdough is controlled by the fermentation conditions and the choice of raw materials, the industrial production of sourdough often relies on single strains of lactobacilli with defined metabolic properties (6, 7).…”
mentioning
confidence: 99%
“…Wickerhamomyces anomalus LCF1695 is, for instance, used as a mixed starter in combination with Lb. plantarum 1A7 [43]; Meyerozyma guilliermondii LCF1353 harbour marked antifungal activity toward P. roqueforti DPPMAF1; sourdough fermented with a combined starter culture-M. guilliermondii LCF1353, W. anomalus LCF1695 and Lb. plantarum 1A7 strain-allows to obtain excellent results in terms of extended shelf-life [44].…”
Section: Sourdoughmentioning
confidence: 99%
“…Several recent studies have addressed the use of metabolites from sourdough lactic acid bacteria and yeasts alone and in combination with natural preservatives, which were extracted from plant materials or were contained in pseudocereals used in the formula for making baked goods (1,2,6,7,8,12,13). Despite promising results, the problem of fungal contamination, of great concern to both consumers and bakeries, still remains unsolved.…”
mentioning
confidence: 99%
“…Sourdough was also considered for extending the shelf life of baked goods. In particular, sourdough lactic acid bacteria synthesize a broad range of antifungal compounds, such as phenyllactic acid, peptides, cyclic dipeptides, and short or medium-chain fatty acids (2,6,7,8,9,10,11).Several recent studies have addressed the use of metabolites from sourdough lactic acid bacteria and yeasts alone and in combination with natural preservatives, which were extracted from plant materials or were contained in pseudocereals used in the formula for making baked goods (1,2,6,7,8,12,13). Despite promising results, the problem of fungal contamination, of great concern to both consumers and bakeries, still remains unsolved.…”
mentioning
confidence: 99%